Role of Education in the Empowerment of Women in India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Women education in India has a major preoccupation of both the government and civil society as educated women can play a very important role in the development of the country. Education is milestone of women empowerment because it enables them to responds to the challenges, to confront their traditional role and change their life. So that we can't neglect the importance of education in reference to women empowerment and India poised to becoming superpower in recent years. Education of women is the most powerful tool to change the position in society. Women education in India has been a need of the hour, as education is a foundation stone for the empowerment of woman.. Education also brings a reduction in inequalities and functions as a means of improving their status within the family and develops the concept of participation. Keywords: Education, preoccupation, milestone, empowerment, participation.